What is parenthood? : contemporary debates about the family - Appleton, Susan Frelich (Families, Law, and Society Series, 2013)
"Extraordinary changes in patterns of family life--and family law--have dramatically altered the boundaries of parenthood and opened up numerous questions and debates. What is parenthood and why does it matter? How should society define, regulate, and support it? Is parenthood separable from marriage--or couplehood--when society seeks to foster children's well-being? What is the better model of parenthood from the perspective of child outcomes? Intense disagreements over the definition and future of marriage often rest upon conflicting convictions about parenthood. What Is Parenthood? asks bold and direct questions about parenthood in contemporary society, and it brings together a stellar interdisciplinary group of scholars with widely varying perspectives to investigate them. Editors Linda C. McClain and Daniel Cere facilitate a dynamic conversation between scholars from several disciplines about competing models of parenthood and a sweeping array of topics, including single parenthood, adoption, donor-created families, gay and lesbian parents, transnational parenthood, parentchild attachment, and gender difference and parenthood"--